Synthesis, characterization and spectroscopic properties of chiral perylene 3, 4 -dicarboxylic- 9, 10- ((R) - (+) - 1 - Phenylethyl) - carboximide for solar cell applications - Ahmed, Hamidu (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
Perylene chromophoric derivatives are versatile compounds for many applications in various fields. Excellent optical properties such as high extinction coefficients and strong fluorescence combined with ease in electron accepting ability are most notable advantages of perylene derivatives. Herein, the project focused on the synthesis of different kinds of perylene dyes, a chiral perylene diimide, a chiral perylene monoimide, and a perylene dicarboxylic acid chiral monoimide, named, N,N′-bis((R)-(+)-1-phenylethyl)-3,4,9,10-perylenebis(dicarboximide) (PDI), N-((R)-(+)-1-phenylethyl)-3,4,9,10-perylenetetracarboxylic-3,4-anhydride-9,10-imide (PMI), chiral perylene-3,4-dicarboxylic -9,10-((R)-1-phenylethyl)carboximide (CPMI), respectively. The final perylene derivative CPMI was synthesized in three consecutive reactions. CPMI was especially designed to be applicable in photovoltaic cells such as dye sensitized solar cells. The synthesized perylene derivatives are characterized in detail by investigating their optical, photophysical, and thermal properties using the techniques FTIR, UV-vis, Fluorescence, DSC, TGA and elemental analysis. They exhibited interesting optical properties, high solubilities, high molar absorption coefficients, and thermal stabilities. Keywords: perylene diimide, perylene monoimide, carboxylic acid monoimde, chiral, extinction coefficient.

ÖZ: Perilen kromoforik türevleri pek çok alanda uygulama olanağına sahip çok yönlü bileşiklerdir. Yüksek molar absorplama sabitleri ve elektron kabul etme kolaylığı ile birlikte güçlü fluoresansa sahip olma gibi özellikler perilen türevlerinin dikkat çeken çok önemli üstünlüklerindendir. Çeşitli perilen boyaların sentezlenmesine odaklanılan bu çalışmada, yeni bir kiral perilen diimid (N,N′-bis((R)-(+)-1-phenylethyl)-3,4,9,10-perylenebis(dicarboximide) (PDI)),, kiral bir perilen monoimid (N-((R)-(+)-1-phenylethyl)-3,4,9,10-perylenetetracarboxylic-3,4-anhydride-9,10-imide (PMI)) ve bir kiral perilen dikarboksi asit monoimid (perylene-3,4-dicarboxylic -9,10-((R)-1-phenylethyl)carboximide (CPMI)). Son sentezlenen perilen türevi olan CPMI üç adımla sentezlenmiştir. Boya duyarlı güneş pilleri gibi fotovoltaik sistemlerde uygulanabilmesi amacıyla tasarlanmıştır. Sentezlenmiş olan perilen türevlerinin optik, fotofiziksel ve termal özellikleri FTIR, UV-vis, Floresans, DSC, TGA ve elementel analiz teknikleri kullanılarak karakterize edilmiştir. Bu maddeler oldukça ilginç optik özelliklerin yanında, yüksek çözünebilirlik, molar soğurma katsayıları ve termal kararlılık göstermektedirler. Anahtar kelimeler: perilen diimid, perilen monoimid, karboksilik asit monoimid, kiralite, soğurma katsayısı.
Master of Science in Chemistry. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2013. Supervisor: Prof. Dr. Huriye Icil.
Keywords: Chemistry; Dyes and Dyeing--Chemistry.; Perylene--Synthesis.; Perylene Diimide; Perylene Monoimide; Carboxylic Acid Monoimde; Chiral; Extinction Coefficient